Authorial Intention Enunciating Through Bakhtin’s Heteroglossia - Varkey, Kuriakose; Sharma, Krishna Kumar; Basak, Sanchari (Cuestiones de Fisioterapia, 2025)
Mikhail Bakhtin, the famous Russian philosopher and critic, explored the term ‘dialogism’ andfound the various dimensions of dialogic communication. Bakhtin says “All words exist indialogue with other words”. Monologism is the one-way traffic of expression from one sideonly and no communication is monologic in any respect. There is no democracy in monologismand the writer never gives the chance to the audience to express their opinion. The power ofopinion should be available to the reader, the narrator, and the writer. In this respect, theinterpretation should come from different persons.